PARAMETER GENETIK SIFAT PERTUMBUHAN DAN KERAPATAN KAYU KLON Eucalyptus pellita F. Muell. DI DUA TAPAK YANG BERBEDA DI KALIMANTAN TIMUR - Achmad Ramadan; Sapto Indrioko; Eko Bhakti Hardiyanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2018)
Industrial forest plantations have an important role in fulfilling the wood demand. Based on global industrial development, the forest plantations industry will increase in the following years. Eucalyptus pellita has become main species in Indonesia forest plantations because it has a short cycle and wood products are suitable to forest industry. The average productivity of E. pellita plantations in Indonesia is still low and high variation. In an effort to increase the productivity, the first step is a better understanding of genetic control on growth and basic density. This study aims to determine the genetic parameters for growth and basic density of E. pellita clones on two different sites. The clonal trials was conducted at two different sites. Both clonal trial are designed using RCBD. The number of clones tested in both trial was 30, 5 blocks and 25 tree/plot. The result of the study showed that the effects of clones vary greatly according the enviromental conditions. The clones- environemntal interaction of growth trait is higher than the basic density. This is in line with genetic parameters of growth trait that are less stable than the basic density. The expected genetic gain of growth trait is higher than the basic density and at the same time there was a weak genetic correlation (there is even a negative) between growth trait and basic density. Therefore carefulness is needed in selecting clones when the two traits are used as selection parameters.